2012
DOI: 10.1539/joh.11-0262-oa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individual and Work‐related Factors on Incidence of Shoulder Pain in a Large Working Population

Abstract: Effects of Individual and Work‐related Factors on Incidence of Shoulder Pain in a Large Working Population: Julie BODIN, et al. LUNAM Université, Université d’Angers, Laboratoire d’ergonomie et d’épidémiologie en santé au travail (LEEST), France— Objectives The aim of this study was to assess the effects of individual and work‐related factors on the incidence of shoulder pain in a large French working population. Methods A total of 3,710 workers of a French region were randomly included in a cross‐sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 37 publications
4
47
2
8
Order By: Relevance
“…En esta misma publicación se encuentra que en España tanto la frecuencia de trabajadores que requerían mantener el nivel de atención elevado, un alto ritmo de trabajo y una elevada cantidad de trabajo eran significativamente mayores que en Navarra. Estos resultados que asocian el nivel de riesgo a la percepción de realización de elevada actividad física coinciden con otros estudios 18 .…”
Section: Discussionunclassified
“…En esta misma publicación se encuentra que en España tanto la frecuencia de trabajadores que requerían mantener el nivel de atención elevado, un alto ritmo de trabajo y una elevada cantidad de trabajo eran significativamente mayores que en Navarra. Estos resultados que asocian el nivel de riesgo a la percepción de realización de elevada actividad física coinciden con otros estudios 18 .…”
Section: Discussionunclassified
“…A follow-up questionnaire was sent to participants in 2007 (22). In this study, only self-administered questionnaires returned ≥3 months before the second physical examination were considered in order to limit the possibility of assessment of risk factors occurring after the second measures of outcome; 59.4% of participants completed a follow-up questionnaire ≥3 months before the second physical examination (ie, 2203 participants, figure 1).…”
Section: Study Populationmentioning
confidence: 99%
“…For example, the longitudinal study found associations between incident self-report shoulder pain, in the week prior to survey, and age, BMI, workplace physical factors, and psychosocial factors among workers at baseline and at three years (68). Extended work schedules (eg, shift work, long hours) were an independent risk factor for MSD among nurses (67), but work schedules are also considered an important occupational risk factor for obesity (see example 2.4).…”
mentioning
confidence: 99%